John Brown - Petrie, Paul R. (The Louisa May Alcott Encyclopedia, 2001)
Louisa May Alcott (1832-1888) is arguably the most widely read 19th-century author in America. Even through the 1990s, her books continued to appear on bestseller lists and her works were made into films. She has long been a staple of children's literature courses and now also receives significant attention in American studies and women's studies classes. While her tremendous popularity has yielded numerous biographies and a growing number of critical works, very few reference books have been devoted to Alcott studies and none are particularly current or complete. This book collects in a comprehensive and reliable single volume the most important facts about Alcott's life and works.This reference surveys the basic biographical details about Alcott's family and personal life. It supplies essential information on her historical and cultural contexts, including her place in the 19th century publishing milieu, various reform movements, and major historical events, such as the Civil War. It also treats her writings, both the adult and children's works, in an accurate, informative, and accessible manner. The volume includes more than 600 alphabetically arranged entries. Each entry discusses the topic's relevance to Alcott's life and current scholarship about her. Many of the entries close with brief bibliographies, and the book concludes with a list of works for further reading.
Keywords: Literary Criticism / American / General; Literary Criticism / General